Environmental Factors in Headache - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
The environmental conditions related to headache in 38 children are reviewed from the Illinois Institute of Technology and the Franciscan Children's Hospital and Rehabilitation Center, Boston, MA.